Generation of vascularized pancreatic progenitors through co-differentiation of endoderm and mesoderm from human pluripotent stem cells - Xiaopu Sang; Junming Xu; Yihang Wang; Jingyi Li; Jiasen Xu; Xiaoni Chen; Xianjie Shi; Fenfang Wu (Stem Cell Research & Therapy)
Abstract Background The simultaneous differentiation of human pluripotent stem cells (hPSCs) into both endodermal and mesodermal lineages is crucial for developing complex, vascularized tissues, yet poses significant challenges. This study explores a method for co-differentiation of mesoderm and endoderm, and their subsequent differentiation into pancreatic progenitors (PP) with endothelial cells (EC). Methods Two hPSC lines were utilized. By manipulating WNT signaling, we optimized co-differentiation protocols of mesoderm and endoderm through adjusting the concentrations of CHIR99021 and mTeSR1. Subsequently, mesoderm and endoderm were differentiated into vascularized pancreatic progenitors (vPP) by adding VEGFA. The differentiation characteristics and potential of vPPs were analyzed via transcriptome sequencing and functional assays. Results A low-dose CHIR99021 in combination with mTeSR1 yielded approximately 30% mesodermal and 70% endodermal cells. Introduction of VEGFA significantly enhanced EC differentiation without compromising PP formation, increasing the EC proportion to 13.9%. Transcriptomic analyses confirmed the effectiveness of our protocol, showing up-regulation of mesodermal and endothelial markers, alongside enhanced metabolic pathways. Functional assays demonstrated that vPPs could efficiently differentiate into insulin-producing β-cells, as evidenced by increased expression of β-cell markers and insulin secretion. Conclusion Our findings provide a robust method for generating vPPs, which holds significant promise for regenerative medicine applications, particularly in diabetes treatment.